2017
DOI: 10.1039/c7ta00389g
|View full text |Cite
|
Sign up to set email alerts
|

Aminated poly(vinyl chloride) solid state adsorbents with hydrophobic function for post-combustion CO2capture

Abstract: The paper presents a novel sustainable route for the production of carbon capture materials from general plastic waste.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Their results also suggested that hybrid functionalization is more useful to produce CO2 adsorbents from PE-MCM-41 with higher performance than their grafted or impregnated counterparts. The synergistic effect of other N-containing materials, including ionic liquids to promote the adsorption capacity of MCM-41, were also studied [54,72,73].…”
Section: Silica Supportsmentioning
confidence: 99%
“…Their results also suggested that hybrid functionalization is more useful to produce CO2 adsorbents from PE-MCM-41 with higher performance than their grafted or impregnated counterparts. The synergistic effect of other N-containing materials, including ionic liquids to promote the adsorption capacity of MCM-41, were also studied [54,72,73].…”
Section: Silica Supportsmentioning
confidence: 99%
“…The synthesis scheme was based on a simple one‐step reaction, which allowed it to be scalable for the further development of industrial CO 2 capture and storage units. Moreover, compared with un‐functionalized mesoporous substrates, aminated PVC adsorbent was found to have exceptional hydrophobic characteristics which enable it to be used in elevated moisture content flue gases …”
Section: Promising Approachesmentioning
confidence: 99%
“…Moreover, compared with un-functionalized mesoporous substrates, aminated PVC adsorbent was found to have exceptional hydrophobic characteristics which enable it to be used in elevated moisture content flue gases. 87 In Europe, recovery of 69.2% of post-consumer plastics was accomplished via energy recovery processes and recycling, whereas the disposal of the rest, 30.8%, took place together with the municipal solid wastes in landfills which in return reduced the landfill capacity as a result of low solid waste density, in 2014. 88 Fu et al reported a technique for the synthesis of hyper crosslinked polymers using Friedel-Crafts reaction employing waste-expanded polystyrene foam as raw material and 1,2-dichloroethane as both solvent and crosslinker.…”
Section: Carbon Capture Using Waste Plastic Sourcesmentioning
confidence: 99%
“…Establishing a sustainable approach to the recycling of waste PVC is of great interest to the environmental communities. For example, a convenient route has been developed to bond amines and alkyl chloride groups by nucleophilic substitution reactions through secondary chlorine groups in the PVC backbone [ 18 ]. Polyethylenimine (PEI) is an amine-rich water-soluble polymer that is widely used for surface modification [ 19 ].…”
Section: Introductionmentioning
confidence: 99%